Physical culture and professional sport motivational factors for engaging engineering students in health-oriented and recreational sectional physical education activities - Pavliuk, Iryna; Kulhuk, Dmytro (My University, 2026)
The formation of a sustainable need for physical activity is one of the key objectives of the physical education system in higher education institutions. Under conditions of intensified academic processes, digitalization of education, and increasing psycho-emotional workload, a decline in the level of physical activity among student youth is observed. The issue of engaging students of technical specialties, whose academic activities are characterized by a high proportion of sedentary work, in systematic physical education classes is becoming particularly relevant. Формування стійкої потреби у фізичній активності є одним із ключових завдань системи фізичного виховання у вищих навчальних закладах. В умовах інтенсифікації навчальних процесів, цифровізації освіти та зростання психоемоційного навантаження спостерігається зниження рівня фізичної активності серед студентської молоді. Особливої ​​актуальності набуває питання залучення студентів технічних спеціальностей, навчальна діяльність яких характеризується високою часткою сидячої роботи, до систематичних занять фізичною культурою.
Keywords: кафедра фізичного виховання; physical education; фізична активність; фізичне виховання; фізичне виховання